2016
DOI: 10.1016/j.cub.2016.03.030
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot-Based Mechanism for Celestial Orientation

Abstract: In order to protect their food from competitors, ball-rolling dung beetles detach a piece of dung from a pile, shape it into a ball, and roll it away along a straight path [1]. They appear to rely exclusively on celestial compass cues to maintain their bearing [2-8], but the mechanism that enables them to use these cues for orientation remains unknown. Here, we describe the orientation strategy that allows dung beetles to use celestial cues in a dynamic fashion. We tested the underlying orientation mechanism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 48 publications
3
90
0
1
Order By: Relevance
“…Some animals used both cues during flight, while other individuals relied predominantly on the simulated sun or the panoramic skyline as a reference. This indicates that the butterfly’s compass is capable of combining and weighting different visual cues, similar to what has been shown in ants and dung beetles (el Jundi et al, 2015b; el Jundi et al, 2016; Huber and Knaden, 2017). This is also similar to findings in the migrating Bogong moth which uses different modalities – the Earth’s magnetic field and dominant visual cues – for orientation (Dreyer et al, 2018a).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some animals used both cues during flight, while other individuals relied predominantly on the simulated sun or the panoramic skyline as a reference. This indicates that the butterfly’s compass is capable of combining and weighting different visual cues, similar to what has been shown in ants and dung beetles (el Jundi et al, 2015b; el Jundi et al, 2016; Huber and Knaden, 2017). This is also similar to findings in the migrating Bogong moth which uses different modalities – the Earth’s magnetic field and dominant visual cues – for orientation (Dreyer et al, 2018a).…”
Section: Discussionsupporting
confidence: 78%
“…In nature, due to a different ratio of shorter (UV light) and longer (green light) wavelengths of light between the solar and anti-solar hemisphere, the direction of the sun can be determined based on a spectral contrast (Coemans et al, 1994; el Jundi et al, 2014). Whether monarch butterflies can use this spectral information, similar to what has been shown for bees (Brines and Gould, 1979; Edrich et al, 1979; Rossel and Wehner, 1984) and dung beetles (el Jundi et al, 2015a; el Jundi et al, 2016) remains to be shown in further experiments. In bees, a green light cue is interpreted as the sun while a UV light cue is treated as a patch of the sky somewhere in the anti-sun direction (Brines and Gould, 1979; Edrich et al, 1979; Rossel and Wehner, 1984).…”
Section: Discussionmentioning
confidence: 55%
“…Learning flights of flying hymenoptera include repeated arcs, loops and turn-backs (honeybees : Becker, 1958;Capaldi and Dyer, 1999;Capaldi et al, 2000;Degen et al, 2015Degen et al, , 2016Lehrer, 1991Lehrer, , 1993Opfinger, 1931;Vollbehr, 1975;wasps: Peckham and Peckham, 1898;Stürzl et al, 2016;Tinbergen, 1932;Zeil, 1993a,b;Zeil et al, 1996;bumblebees: Collett et al, 2013;Hempel de Ibarra et al, 2009;Philippides et al, 2013;Riabinina et al, 2014;Robert et al, 2017;Wagner, 1907). Dung beetles perform rotations about their vertical axis before rolling a ball away from the dung pile (Baird et al, 2012), during which they take a snapshot of the celestial scenery (el Jundi et al, 2016). Desert spiders also perform learning walklike behavior: they leave their burrows in sinusoidal paths when departing to unfamiliar terrains (Nørgaard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interessanterweise rotieren auch Dungkäfer um 360° auf ihrer Dungkugel, um ihren Himmelskompass so einzurichten, dass sie sich anschließend geradlinig mit ihrer Dungkugel fortbewegen. Bevor sie mit ihrer Kugel losrollen, speichern sie den jeweils aktuellen Sonnenstand ab . Bei einer Pirouette hingegen bleiben die Ameisen stehen und drehen sich um ihre vertikale Körperachse.…”
Section: Volten Und Pirouettenunclassified